Nitrate remediation in a novel upflow bio-electrochemical reactor (UBER) using palm shell activated carbon as cathode material - Ghafari, S.; Hasan, M.; Aroua, M.K. (Elsevier, 2009)
This study investigated the biological denitrification method which is a treatment method able to reduce inorganic nitrate compounds to harmless nitrogen gas. Autohydrogenotrophic denitrifying bacteria were used in this study to prevent any problematic outcomes associated with heterotrophic microorganisms. An upflow bio-electrochemical reactor (UBER) was used to accommodate hydrogenotrophic denitrifying bacteria employing palm shell granular activated carbon (GAC) as the biocarrier and cathode material. Bicarbonate as the external inorganic carbon source was fed to the reactor and hydrogen as the electron donor was generated in situ through electrolysis of water. Central composite design (CCD) and response surface methodology (RSM) were applied to investigate the effects of two operating parameters, namely electric current (I) and hydraulic retention time (HRT), on performance of the UBER. Electric current range of 0-20 mA and HRT range of 6-36 h were examined and results showed that nitrate can be entirely reduced within application of a wide operational range of electric current (10-16 mA) as well as HRT (13.5-30 h). However, increase of pH at cathode zone up to 10.5 inhibited nitrite reduction, and it was not reduced to the satisfactory level.